Number System and Its Importance - Husenova Dilora Mirzayevna (Euro Asian Journal Publishing, 2024)
This article provides an in-depth exploration of the intrinsic concept of the number system and its pivotal significance across a spectrum of disciplines, including mathematics, computer science, engineering, and scientific research. By delving into various numerical bases such as decimal, binary, octal, and hexadecimal, the discussion aims to illuminate the diverse applications and adaptability of the number system. The emphasis lies on elucidating the critical role that a comprehensive understanding of the number system plays in facilitating precision and efficiency. In the realm of mathematics, the number system acts as the bedrock for advanced calculations, algebraic manipulations, and intricate problem-solving.
Keywords: Number System; Decimal; Binary